(untitled) (Delito y Sociedad, 2020)
The aim of this work is the study of Police Tactical Groups in Argentina, based on the field work carried out in the GEOF group, of the Argentine Federal Police, and the UESPO group, of the Police of Neuquén Province. e main objective is to carry out a characterization of their forms of policing, om the description and analysis of the way they are organized and act, as well as the understandings that the tactical troops express in relation to their work. In order to do this, we will explain their particular recruitment processes, the way they train, and the way they deploy as a group. en we will analyze the special police culture that is cultivated in these spaces, based on a reconceptualization of this notion through the use of Bourdieu’s idea of class habitus. us, we will describe the special relationship established by the tactical troops with the idea of «real police work», the relationships of companionship and internal solidarity that they develop, the elitist character they attribute to this space and certain features that configure what we call «tactical habitus».